COMPARATIVE STUDY OF COMMUNICATIVE-PRAGMATIC TYPES OF COMPOUND SENTENCES WITH CAUSATIVE-CONSECUTIVE RELATIONS IN ENGLISH AND UZBEK (SCIENCE TIME JOURNAL, 2026)
This study examines the compound sentences with causative‐consecutive relations in English and Uzbek, focusing on their communicative‐pragmatic types. Drawing on theories from contrastive and cognitive linguistics, the analysis compares the composite sentence systems of the two languages, with particular attention to the positioning and number of conjunctions, the use of tense, and the overall syntactic structure. While both languages share a common function in expressing cause and effect, marked differences are evident in the placement of conjunctions, reliance on inflection versus word order, and tense agreement across clauses. The findings underscore the challenges inherent in translating such structures between English and Uzbek and suggest implications for language instruction and further research in interlingual grammar.